WORKSHOP PENINGKATAN KAPASITAS PENGURUS KELOMPOK DEBITUR/PENERIMA MANFAAT UPK – PDB DAPM Kec. KALIJAMBE, SRAGEN - T.D.K.W, Yuniatin; .Khoiruman, Muh; Fathonah, Siti; Wariati, Ambar; Lathifah, Ifah; Pamungkas, Anton Respati (LPPM Institut Teknologi dan Bisnis Kristen Bukit Pengarapan, 2024)
Sragen district has 18 Activity Management Units (UPK) of PDB in 18 districts with the highest fund value in Kalijambe. In 2023 there was a delay/failure to pay because the turnover of funds had not been used for business development and only for consumer activities, as well as loan funds were not used to add capital. Fund management is still done manually and the managers has no knowledge of financial management/ accounting records. The activity held in September 2023 with 31 participants head and treasurer of SPP Beneficiaries in the village of Wonorejo, Kalijambe. Data collection through interviews, observations and documentation. Activity methods with workshop and training. The activity aims to improve the capacity of managers of Benefits by providing workshop/training of loan management techniques, how to conduct business activities and policies, ways to organize and organize business organization, as well as how to use simple accounting for activities so as to minimize the possibility of failure to pay/default.